The use of YouTube as Learning Media to Enhance the Students’ skill in Writing Expository Text - Suerni Suerni (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study explored the effectiveness of YouTube as a learning medium to improve students’ skills in writing expository text. As a widely accessible audiovisual platform, YouTube offers rich, engaging content that can support students in understanding complex topics, organizing ideas, and presenting information clearly. By integrating YouTube videos into writing instruction, the lecturer can provide real-world examples, stimulate critical thinking, and enhance students’ motivation to write. This study used a classroom action research method over two cycles with the second semester students of Institute of Health and Technology, Ika Bina Labuhan Batu. Initially, students showed weak writing ability (average score: 52.1). After introducing the video of social phenomenon by YouTube, there was a significant increase in learning outcomes—scores rose to 74.4 in the first cycle and 85.3 in the second. The use of audiovisual media made learning more engaging, increased student participation, and improved coherence, diction, and grammar in writing. By the end of the study, 91% of the students of met or exceeded the passing score.